Más allá de la utopía : Agrupación Guerrillera de Levante / Fernanda Romeu Alfaro ; prólogo, Antonio María Calero ; fotografías, José M Azkárraga - Calero Amor, Antonio MaríaAzkárraga, José María; Romeu Alfaro, Fernanda (Almud; 1)
Fuentes y bibliografía: p. [558]-570